PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP TURNOVER INTENTION PADA PELAUT DI PT. MARITIM BARITO PERKASA BANJARMASIN - August Tantowi; Laila Refiana Said; Rini Rahmawati (Universitas Lambung Mangkurat, 2016)
This research aims to identify and analyze the influence financial compensation and non financial compensation as an independentvariable to job satisfaction as intervening variable and the impact to turnover intention as dependen variable of on duty sailors at PT. Maritim Barito Perkasa ships. Research instruments used questionnaire and Likert’sScale as variable measurement on 250 sailors as a sampleas to the characteristic of sailors who were on duty on board from 307 sailors work at PT. Maritim Barito Perkasa. Effect of finansial compensation and non finansial compensation will be tested to job satisfaction and tested the direct effect financial compensation, non financial compensation and job satisfaction to turnover intention as a dependen variable, and tested indirect effect finansial compensation and non financial compensation as variable independentto turnover intention as variable dependent through job satisfaction as intervening variable used Path Analysis on IBM SPSS versi 21 programme. The result of the research concludes that thefinancial compensation and non financial compensation has apositif impact and significantto the job satisfaction. Finansial compensation has negatif significant impact, non financial compensation has negatif not significantimpact and job satisfaction has negatif significantimpact to turnover intention. Job Satisfaction as an intervening variable decrease the effect of financial compensation into the turnover intention, and increase the effect of non financial compensation to turnover intention